COMMUNITY ENGAGEMENT NECESSARY FOR UNIVERSITIES TO REMAIN RELEVANT - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
SURABAYA, INDONESIA, 3 August 2016 – In ensuring the longevity of universities for social development, the institutions would need to engage with various communities within the framework of a holistic global movement.